PERSONAL BRANDING PADA INDUSTRI CITRA - Muhammad Fadeli (J-IKA : Jurnal Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas BSI Bandung, 2014)
Abstract - 2014 was a golden year for the media industry, where the mass media will dredge the many advantages of the legislative candidates who require self-image. Whatever will be done in order to captivate the public's attention and lead public opinion to public finally decided to throw in them. The candidates for local and national leaders have started to play a role as a public figure who sell the image to draw public sympathy. Understand that level of fame, popularity of the figure's head is an important factor, the political vehicle, regional head candidates scoring machine must perform the steps in a systematic and strategic campaigning as the popularity does notcome just like that. At issue is when the popularity is not supported by the capability of the leader. So just as the party or coalition of parties presenting a blank check to the people. So that the people are not fooled by the jargon of political campaigns, it's time track record of candidates for the leader seen  carefully.  Voters empowered  critically  important that  people  are  getting smarter and not mobilized on a particular political force or even mobilized by the power of capital owners. And it is time for the candidates for the legislative candidates to improve itself, instead of just  selling  the  image,  competing  to  display  their best  photos,  they  put  forward  the  size  ofbillboards, and so forth. Because people are not public or packaging buyers, but those buyers contents.  Keywords : Campaign, Popularity, Capability   Abstrak - Tahun 2014 adalah tahun emas bagi industri media massa, dimana media massa akan mengeruk banyak keuntungan dari para calon anggota legislatif yang membutuhkan pencitraan diri. Apapun akan dilakukan demi memikat perhatian publik dan menggiring opini publik sampai akhirnya publik menjatuhkan pilihannya pada mereka. Para calon pemimpin lokal maupun pusat sudah mulai memainkan peranannya sebagai seorang public figure yang menjual image untuk menarik  simpati public.  Memahami bahwa tingkat ketenaran, popularitas  figur  kepala daerah adalah faktor penting,  kendaraan politik, mesin gol calon kepala daerah harus melakukan langkah - langkah sistematis dan strategis dalam berkampanye karena popularitas tidak datang begitu saja. Yang menjadi persoalan adalah  ketika popularitas tidak ditunjang oleh  kapabilitas pemimpin. Maka sama halnya partai atau koalisi partai menyuguhkan cek kosong kepada rakyat. Agar rakyat tidak tertipu oleh jargon-jargon kampanye politik, sudah saatnya rekam jejak calon anggota pemimpinnya dilihat secara seksama. Pemilih kritis penting diberdayakan agar rakyat semakin cerdas  dan  tidak  termobilisasi  pada  kekuatan  politik  tertentu  atau  bahkan  termobilisasi  oleh kekuatan pemilik modal. Dan sudah saatnya para calon calon anggota legislatif tersebut berben ah diri, bukan hanya sekedar menjual citra, berlomba-lomba menampilkan foto terbaiknya, saling adu ukuran baliho, dan lain sebagainya. Sebab publik atau rakyat bukanlah pembeli kemasan, tapi mereka pembeli isi.  Kata Kunci : Kampanye, Popularitas, Kapabilitas